The Prophet Muhammad SAW Rahmatan lil Armalati wal Masakini: A Study of the Book of Rahmatan lil-'Ālamīn by Sa'īd bin 'Alī al-Qaḥṭānī - Bakhrul Ilmi Dhul Fahmi; Basuki Basuki (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The vulnerability of widows (al-armalah) and the poor (al-masākīn) remains a significant challenge in contemporary social welfare, while the concept of Raḥmatan lil Armalati wal Masākīn has received limited scholarly attention as an Islamic social protection paradigm. This study examines the conceptual framework of protecting widows and the poor in Rahmatan lil-'Ālamīn by Sa'īd bin 'Alī al-Qaḥṭānī and its relevance to contemporary social welfare. Using a qualitative library research approach, data were collected from primary and supporting literature and analyzed through Krippendorff's qualitative content analysis with source triangulation. The findings reveal that al-armalah represents not merely a demographic category but a vulnerable group requiring integrated economic, social, and psychological protection. The practices of Prophet Muhammad SAW and the policies of Umar ibn al-Khaṭṭāb demonstrate a social protection model grounded in theological values, social ethics, empowerment, and public responsibility. The study's novelty lies in reconstructing Raḥmatan lil Armalati wal Masākīn as a conceptual framework that bridges prophetic values with contemporary social protection, providing a foundation for more inclusive, equitable, and sustainable welfare policies.